Ciało - źródło grzechu czy powód do chwały w świetle poglądów Tertuliana - Adam M. Filipowicz (Studia Ecologiae et Bioethicae)
The article considers human body in teaching of Tertullian, one of the famous early Christian writers and an important apologist of Christianity. It consists of five parts: 1. Introduction; 2. Despise body in ancient philosophical thought; 3. Dignity of body according to Tertullian; 4. Human body and responsibility for evil and sin; 5. Summary.